Efficacy of the feed additive consisting of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) CECT 8350 and Limosilactobacillus reuteri (formerly Lactobacillus reuteri) CECT 8700 (AQ02) for suckling piglets (Aquilon Cyl S.L.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the feed additive consisting of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) CECT 8350 and Limosilactobacillus reuteri (formerly Lactobacillus reuteri) CECT 8700 (AQ02) as a zootechnical feed additive for suckling piglets. In a previous opinion the FEEDAP Panel concluded that the additive is considered safe for the target species, the consumer, and the environment. The Panel concluded that the additive should be considered a respiratory sensitiser but could not conclude on the skin/eye irritation potential or on its skin sensitisation potential. The Panel previously could not conclude on the efficacy of AQ02. The applicant has provided supplementary information to support the efficacy of the additive in suckling piglets. Based on the data provided, the FEEDAP Panel could not conclude on the efficacy of the additive.